Influence of fiber degradation and concentration of fermentable sugars on simultaneous saccharification and fermentation of high-solids spruce slurry to ethanol - Hoyer, Kerstin (BioMed Central, 2013)
BACKGROUND: Saccharification and fermentation of pretreated lignocellulosic materials, such as spruce, should be performed at high solids contents in order to reduce the cost of the produced bioethanol. However, this has been shown to result in reduced ethanol yields or a complete lack of ethanol production. Previous studies have shown inconsistent results when prehydrolysis is performed at a higher temperature prior to the simultaneous saccharification and fermentation (SSF) of steam-pretreated lignocellulosic materials. In some cases, a significant increase in overall ethanol yield was reported, while in others, a slight decrease in ethanol yield was observed. In order to investigate the influence of prehydrolysis on high-solids SSF of steam-pretreated spruce slurry, in the present study, the presence of fibers and inhibitors, degree of fiber degradation and initial fermentable sugar concentration has been studied. RESULTS: SSF of whole steam-pretreated spruce slurry at a solids content of 13.7% water-insoluble solids (WIS) resulted in a very low overall ethanol yield, mostly due to poor fermentation. The yeast was, however, able to ferment the washed slurry and the liquid fraction of the pretreated slurry. Performing prehydrolysis at 48°C for 22 hours prior to SSF of the whole pretreated slurry increased the overall ethanol yield from 3.9 to 62.1%. The initial concentration of fermentable sugars in SSF could not explain the increase in ethanol yield in SSF with prehydrolysis. Although the viscosity of the material did not appear to decrease significantly during prehydrolysis, the degradation of the fibers prior to the addition of the yeast had a positive effect on ethanol yield when using whole steam-pretreated spruce slurry. CONCLUSIONS: The results of the present study suggest that the increase in ethanol yield from SSF when performing prehydrolysis is a result of fiber degradation rather than a decrease in viscosity. The increased concentration of fermentable sugars at the beginning of the fermentation phase in SSF following prehydrolysis did not affect the overall ethanol yield in the present study.